Medical and nursing students' co-learning in digitalized health care eco-system - Nina Smolander; Tuomas Koskela; Ilona Jylhäsalo; Taru Manner; Mervi Kautto; Riikka Riihimies (Finnish Social and Health Informatics Association, 2022)
The demographic change in Finnish population has forced us to develop digital solutions to meet health care requirements. To respond to the need, we designed and piloted a one-day Multidisciplinary Digital Clinic (MDC) education for medical and nursing students. In this report, we describe our project of the one-day MDC education of digital solutions in primary care for medical and nursing students, and their learning experiences. Additionally, we describe the realization of the intended learning outcomes. The MDC education was conducted by flipped learning method with pre-studying materials. The MDC day was divided into three topical workshops: Remote Care, Digital Symptoms and Health care assessment, and Assessment of Need for care. Students formed three multidisciplinary teams. The students (N=108) valued the opportunity to train with modern technological equipment. Learning in the multidisciplinary teams enabled their knowledge and expertise sharing beyond study field limits, and provided a unique opportunity to discuss together, and thus, helped generate future-proof cooperation skills. The MDC training improved students' understanding of digitally enhanced health care services and increased their understanding of the automated digitalized service pathways, and the continuity of care. In conclusion, the students described MDC as a unique opportunity, and future oriented education. The MDC encouraged students to get involved in the digitally and technologically enhanced health care eco-system in their professional careers.